Strategi branding membangun Brand Identity pada UMKM - Ayu Oktavianingrum; Dwi Nur Hidayati; Ertien Rining Nawangsari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The development of the times requires introducing its products more easily and modernly to consumers through a brand. The writer who did community service in Nglebak Village, Jombang Regency found the problem of a Brand Identity that was not yet known by MSME owners, so it was sparked to help several MSMEs in introducing what Brand Identity was. With the method 1) Socialization of UMKM inviting a resource person in their field, 2) Followed by assistance in making UMKM Brand Identity, and 3) Inauguration of 3 Brand Identity accompanied by physical handover to 3 (three) UMKM, namely a) Pesona Mebel, Mr. Suparno's business which operates on furniture or furniture made of teak wood, b) Snacks from Mrs. Seniti, a culinary business with the superior product banana chips from Mrs. Seniti, and c) Rahayu Wilujeng Salted Egg owned by Mr. Muslimin who processes his home-breed duck eggs into ready-to-eat salted eggs. As a result, UMKM in Nglebak Village, who previously did not know the importance of brand identity, are now able to understand the importance of a Brand Identity after following the stages of the author's method of implementing community service. With the Identity Brand which is starting to be built, it is hoped that it will be able to sustain the UMKMbusiness.